THE ADAPTATION OF THE US ARMY TO THE BATTLEFIELD OF THE XXI ST CENTURY - GUILLEM COLOM PEILLA (Política y Estrategia, 2017)
Since the fall of the Berlin Wall, the U.S. Army has undertaken significant changes in its military thought, strategic planning, doctrinal foundations, weapon systems and organizational structures in order to achieve the Revolution of Military Affairs that promised to change the art of war; to adapt its forces to the post-Cold War strategic environment; to face uncertain future challenges and, now, to overcome the operational requirements stemming from its involvement in Afghanistan and Iraq.